Neither stable nor pristine: American bison populations were long influenced by humans - Shaw, James H (THERYA, 2021)
Populations of North American bison (Bison bison) are widely presumed to have remained stable, numbering in the tens of millions, right up until the hide hunts of the 1870s nearly brought about extinction. Recent scholarship from various disciplines consistently undermines this presumption. Indigenous people likely affected bison populations from their arrival toward the end of the Pleistocene. By the time of Columbus, indigenous populations were high and their impacts were felt keenly. As documented in the 16th century journals of Cabeza de Vaca, big game populations, including bison, were suppressed by hunting. That changed, however, with arrival of Old World diseases that are estimated to have reduced indigenous populations in the Americas by 90 % within a century of contact with Europeans. Such drastic reductions in indigenous human populations allowed bison populations to expand. Gradually, increased pressure from human hunters, along with competition from feral horses, introduced infectious diseases, habitat changes, and droughts, all suppressed bison populations well before the notorious hide hunts began in the 1870s. The hide hunts were the final blow to free-ranging bison, but reduced populations in the decades prior paved the way and helps explain why bison were reduced to near extinction within a few years.